Dijkstra-based Official Motorcycle Repair Shop Application for Determining the Shortest Route - Sucipto, Adi; Doheir, Mohamed (Universitas Dian Nuswantoro and IndoCEISS, 2023)
Servicing on 2-wheeled vehicles is needed so that the condition remains prime and minimizes the symptoms of component damage. Motorcycle service activities have an impact on the automotive world, especially in the City of Kudus. There are also many motorized vehicle users who do not know the closest route to the nearest Authorized Motorcycle Workshop in the holy city and choose Engine Fuel (BBM) that is in accordance with the type of vehicle they have. shorter service life because the RON (Research Octane Number) or octane number for each motorized vehicle is different, the octane number represents the resistance of the fuel to engine compression. With the development of information science in the current era, an Android-based application was created to search for the closest route to an official motorcycle repair shop in the Kudus City using the Djikstra Algorithm and having a BBM recommendation feature that is suitable for motorbike users' vehicles in the Kudus City.